Pyroptosis in periodontitis: From the intricate interaction with apoptosis, NETosis, and necroptosis to the therapeutic prospects - Xu, Xiaohui; Zhang, Tingwei; Xia, Xuyun; Yin, Yuanyuan; Yang, Sihan; Ai, Dongqing; Qin, Han; Zhou, Mengjiao; Song, Jinlin (Frontiers in Cellular and Infection Microbiology, 2022)
Periodontitis is highly prevalent worldwide. It is characterized by periodontal attachment and alveolar bone destruction, which not only leads to tooth loss but also results in the exacerbation of systematic diseases. As such, periodontitis has a significant negative impact on the daily lives of patients. Detailed exploration of the molecular mechanisms underlying the physiopathology of periodontitis may contribute to the development of new therapeutic strategies for periodontitis and the associated systematic diseases. Pyroptosis, as one of the inflammatory programmed cell death pathways, is implicated in the pathogenesis of periodontitis. Progress in the field of pyroptosis has greatly enhanced our understanding of its role in inflammatory diseases. This review first summarizes the mechanisms underlying the activation of pyroptosis in periodontitis and the pathological role of pyroptosis in the progression of periodontitis. Then, the crosstalk between pyroptosis with apoptosis, necroptosis, and NETosis in periodontitis is discussed. Moreover, pyroptosis, as a novel link that connects periodontitis with systemic disease, is also reviewed. Finally, the current challenges associated with pyroptosis as a potential therapeutic target for periodontitis are highlighted.